Management of a patient with Trigeminal Neuralgia associated with failed endodontic therapy using Ozone Therapy: A Case Report (Ozone Therapy Global Journal, 2018)
Trigeminal Neuralgia (TN) is a painful disorder that can affect one or more branches of the fifth cranial nerve. Pain may be triggered by normal mechanical or sensory stimuli or may be spontaneous. This case report describes the management of a patient that presented with a 10 year history of constant dull pain with mechanical and sensory stimuli of acute, sharp pain along the distribution of the third division of the right trigeminal nerve. The onset of pain was associated with root canal therapy on tooth # 30 (IS-46). The patient had received pharmacological and surgical interventions some of which had provided temporary relief, but the pain had always returned and steadily increased over time. Radiographically, the tooth presented with evidence of apical lesions because of root canal failure. Based on clinical and animal studies, it is known that areas of chronic osseous infection or mechanical compression produce elevated levels of reactive oxygen species, and other tissue degradation products that could be responsible for pathological changes in the nerve fibers, resulting in chronic pain.Medical oxygen/ozone (MOZO) is a medical modality that has been demonstrated to have multiple local and systemic effects, including analgesia and reduction of inflammation. Major autohemotherapy is one of the method of systemic delivery of MOZO that can applied to treat conditions that are a result of chronic oxidative stress. This case report describes how major autohemotherapy was used to facilitate the resolution of TN that was the result of a chronic dental infection.